Ring opening copolymerization of δ-valerolactone with 2-methyl-1, 3-dioxane-4-one towards poly(3-hydroxypropionate-co-5-hydroxyvalerate) copolyesters. Issue 15 (25th March 2022) - Zhang, Wenli; Han, Li; Liu, Zhipeng; Li, Yidi; Shang, Jingzhao; Leng, Xuefei; Li, Yang; Wei, Zhiyong
Abstract : A straightforward strategy of ring-opening copolymerization (ROCOP) towards synthetic copolyesters. Abstract : A straightforward strategy of ring-opening copolymerization (ROCOP) toward synthetic copolyesters is gaining increasing interest. In the present work, a novel series of poly(3-hydroxypropionate- co -5-hydroxyvalerate) P(3HP- co -5HV) copolyesters are obtained through the ROCOP of a lactone, i.e., δ-valerolactone (δ-VL), with a cyclic hemiacetal ester, i.e., 2-methyl-1, 3-dioxane-4-one (MDO), using diethylzinc (Et2 Zn) as the catalyst and benzyl alcohol (BnOH) as the initiator. Consumption of δ-VL and MDO in the polymerization process is monitored by in situ 1 H NMR spectroscopy. A range of feeding ratios that provide 3-HP/5-HV copolyesters of variable sequence compositions have been used systematically. The non-termination model, appropriate for ideal copolymerization, which is defined by r A × r B = 1, is employed in the analysis of the copolymerization kinetics, i.e., the reactivity ratio ( r ). Effectively, the r MDO and r δ-VL values with r MDO × r δ-VL ∼1 in a range of monomer feed ratios have been established at low conversions. The statistical gradient or near ideal random microstructure of P(3HP- co -5HV) with variable compositions is illustrated through the combination of in situ 1 H NMR and quantitative 13 C-NMR. The (co)polyesters show a narrow polydispersity index (PDI < 1.2) and their molecular weight could be driven by the feed ratio. Furthermore, the crystallization ability of HV and HP comonomers is evaluated as indicated by DSC, WAXD and POM. It appears that the crystallization ability of HV is greater than that of HP, but HV units are inherently difficult in the formation of typically spherical crystals. The insertion–rejection theory has been employed for the analysis of the established pseudo-eutectic point with regard to the T m values occurring at about 42% HV content.